Two-Mode-Dependent Controller Design for Networked Markov System With Time-Delay in Both S/C Link and C/A Link - Yanfeng Wang (IEEE Access, 2020)
The two-mode-dependent controller design problem for networked Markov system with time-delay in both S/C link and C/A link is investigated in this paper. Two independent Markov chains are used to describe the time-delay in S/C link and C/A link. A two-mode-dependent state feedback controller is proposed that depends on both the S/C time-delay and the mode of the Markov controlled plant. The sufficient conditions on the stochastic stability of the closed-loop system are established. The design method of the controller is also proposed on condition that the transition probability matrices of S/C time-delay and mode of the controlled plant are completely known and partly unknown respectively. A numerical example is exploited to illustrate the effectiveness and superiority of the proposed method.